Forms of cross-border cooperation based on the example of the Baltic commune of Heringsdorf (Germany) and Świnoujście (Poland) - Tobolska, Anna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The article is part of the socio-economic analysis of the so-called Border Studies and concerns cross-border links and the processes of creating trans-local spaces. The main objective is to analyse various forms of cross-border cooperation, which as a result lead to the thickening of social, cultural and economic contacts between neighbouring communities on both sides of the border, and thus to the blurring of its formal character. The cross-border microregion on the Pomeranian Bay of the Baltic Sea, lying on both sides of the Polish-German border, consisting of neighbouring communes: Heringsdorf on the German side of the border and the commune of Świnoujście on the Polish side, was selected as the research object. The selected micro-region can be a characteristic example of the creation of transnational and translocal spaces, because as a result of integration treaties within the EU, the border has suddenly lost the power of an impenetrable barrier, and additionally, the attractive tourist location contributes to a more intensive functional link between the two communities. Based on a detailed empirical analysis of many recognised forms of cross-border cooperation, an attempt was made to systematise them in several spheres: economic, social, cultural and sports, and institutional. The study mainly used social research methods, i.e. field observation and in-depth interviews, as well as an analysis of official and media reporting documents.